Reforming State Administration Law in the Digital Era: The Impact on Public Policy Efficiency - Arifin, Firdaus (Faculty of Law, Universitas Pekalongan, 2024)
The evolution of state administrative law in the digital era has become imperative to accommodate the ever-changing advancements in technology. Utilising technology in public administration can improve accountability, transparency, and public participation. The objective of this study is to examine the necessity of reform in state administrative law in Indonesia in response to the problems posed by the digital era, specifically in relation to the execution of technology-driven public policy. The strategy employed is a normative legal methodology, which involves analysing literature and relevant rules. The research findings suggest that the existing legislative framework for administration does not adequately facilitate the efficient deployment of digital technologies in government. There is a pressing requirement for the establishment of regulations that are more suited to accommodate technological progress. This research highlights the significance of law reform and the establishment of digital infrastructure that enhances the efficiency of government in Indonesia. This change is anticipated to bolster accountability and transparency in the formulation of public policies, while also fostering greater community participation in the governing process.